COMPARANDO TRANSMISIONES DEPORTIVAS: INDICADORES DE ESTILO EN LA PUESTA EN PANTALLA DEL FÚTBOL EN ARABIA SAUDÍ, INGLATERRA Y ESPAÑA - Dr. Anto J. BENÍTEZ,Ddo. Ángel M. LÓPEZ LÓPEZ,Dr. Manuel SÁNCHEZ CID (Fonseca, Journal of Communication, 2023)
The International Federation Football Association (FIFA) takes over the most homogeneous developing of football as a sport across the world. Even so, players, coaches, audiences and different latitudes stages, shape very different competitions. Sport viewers, using the Media globalization possibilities, are able to distinguish different ways of showing football matches on screen.